Hydrothermal preparation of Sn3O4/TiO2 nanotube arrays as effective photocatalysts for boosting photocatalytic dye degradation and hydrogen production. Issue 4 (15th February 2023) - Wang, Qingyao; Zhao, Yuhua; Zhang, Zifeng; Liao, Shengwen; Deng, Yadan; Wang, Xiang; Ye, Qilu; Wang, Kesheng
Abstract: The efficient TiO2 NTs/Sn3 O4 photocatalysts were synthesized by the hydrothermal deposition of Sn3 O4 on TiO2 nanotube arrays (TiO2 NTs), and the morphology, microstructure and photocatalytic property were adjusted by changing the alkali kind. The TiO2 NTs/Sn3 O4 prepared with NaOH exhibited the outstanding photoelectric conversion and photocatalytic environment remediation/H2 evolution. The methylene blue (MB) dye and Cr(VI) could be removed by the as-prepared photocatalysts under visible light irradiation, and O2 − /OH radicals were the main active species for MB photodegradation. Furthermore, the high photocatalytic H2 evolution rate was as high as 6.49 μmol cm −2  h −1 . The outstanding photocatalytic activity and stability of TiO2 NTs/Sn3 O4 photocatalysts would exhibit attractive prospect in the wastewater remediation and electric energy/hydrogen generation.